Inclusion of Elevation for Backfilling for Building Permit in Contribution to Flood Control in Swamp, Puguis, La Trinidad Benguet - Frankline Bon G. Bahay; Christian Llyod P. Ulbano; Chid Rick C. Cachero; Hudster L. Dati; Faith Tigan; Charlie M. Felix; Criselda S. Felix (Future Science / FSH-PH Publications, 2026)
The study conducted in Swamp, Puguis, La Trinidad, Benguet, evaluated the inclusion of elevation and backfilling requirements in building permits as a flood control measure, revealing strong awareness and positive perceptions among respondents regarding their impact on flood risk reduction. Surveying 41 participants including geodetic engineers, iv government officials, and residents the research found that elevated structures significantly influence natural drainage and surface water flow, with respondents rating their understanding as high. There was overwhelming agreement that backfilling activities that do not comply with proper elevation standards escalate local flood risks, emphasizing the crucial role of geodetic engineers in conducting precise surveys, verifying compliance, and informing policies. Awareness of geodetic engineers’ contributions to flood control was notably strong, and respondents recognized the importance of including elevation certificates in building permits as essential for accurate flood risk assessments and alignment with flood hazard maps. Although the integration of elevation data in permitting processes is seen as largely implemented and valuable for reducing vulnerability to floods, enforcement remains inconsistent, and public education about its benefits requires enhancement. These findings highlight the pressing need for local governments to strengthen technical guidelines, monitoring, and stakeholder engagement to effectively incorporate elevation standards into building permits, promoting sustainable development and fortified flood resilience in flood-prone swamp v areas, with potential applicability to similar urban and rural settings across the Philippines and the broader Asia-Pacific region.